Adult male-specific inverse association between dry eye disease and intraocular pressure: KNHANES 2010–2012 - Yun-Hee Choi; Martha Kim; Yoon-Hyeong Choi; Dong Hyun Kim (PLoS ONE, 2025)
Purpose To investigate the association between dry eye disease (DED) and intraocular pressure (IOP) in the general adult population of South Korea. Methods We enrolled 13,194 adults (age ≥19 years) who had participated in the fifth Korea National Health and Nutrition Examination Survey conducted from 2010 to 2012. IOP was measured using Goldman applanation tonometry. DED was defined as the presence of self-reported symptoms along with a diagnosis by an ophthalmologist. As the correlation between the left and right eyes was high (r = 0.833), only the measurement values of the right eye were used. We sequentially conducted multiple linear and logistic regression analyses to investigate the association between DED and IOP and prevalence of high IOP (>21 mmHg). Results The prevalence of DED in Korean adults was 7.8%, and the geometric mean of IOP in the right eye was 13.7 ± 1.0 mmHg. In the fully adjusted model, participants with DED had a significantly lower IOP compared to those without DED in the overall population (β = -0.032; 95% confidence interval [CI]: -0.059, -0.004). This trend was evident in males (β = -0.059; 95% CI: -0.106, -0.012) but not in females. Similarly, males with DED had a significantly lower prevalence of high IOP compared to those without DED (odds ratio [OR] = 0.18; 95% CI: 0.04, 0.91), but this association was not evident in females. Conclusions This study suggests that DED is associated with lower IOP in adult Korean males.